Determinants of dividend payout ratio in the Malaysian steel industry / Suhaily Maizan Abdul Manaf, Nurul Syuhada Baharuddin and Nurul Fairus Bariah Yahya - Abdul Manaf, Suhaily Maizan; Baharuddin, Nurul Syuhada; Yahya, Nurul Fairus Bariah (2021)
The steel industry around the world is grappling with the effects of COVID-19. The demand growth in 2019 was slower than expected because of the continuing manufacturing recession in developed countries. In the first several months of 2020, other major steel manufacturers recorded a considerable reduction in exports. As a result of this, numerous policies were implemented during the pandemic to support downstream demand. The need arises due to the importance of measuring dividends among shareholders. However, other existing variables need to be studied. Therefore, the rationale of this study is to conduct an empirical analysis on the determinants of the dividend payout ratio of the steel industry in Malaysia. The four determinants identified in this study are profitability, liquidity, leverage, and firm size. Secondary data was collected from 20 steel companies listed in Bursa Malaysia (stock exchange in Malaysia) from 2008 until 2017. Using the regression analysis and Random Effect Model, findings revealed that profitability and liquidity have a positive and significant effect on the dividend payout ratio of the steel industry. In the meantime, firm size shows a positive yet insignificant effect on the dividend payout ratio. Meanwhile, leverage was discovered to have a negative and negligible effect concerning the dividend payout ratio. This study suggests that finance managers must develop a clear dividend policy that specifies the percentage of dividends paid and retained to keep existing shareholders and attract new investors. Moreover, it will also assist them in keeping their existing investors for a longer length of time and attracting new investors to mobilize funds for future initiatives.